Phenolics of Convolvulus arvensis L. and Their Related Pharmacological Activity - Awaad, A.S.; Mohamed, N.H.; El-Sayed, N.H.; Soliman, G.A (Asian Journal of Chemistry, 2010)
The aerial parts, roots and flowers of Convolvulus arvensis L. were investigated for their secondary metabolites. Eleven flavonoids were detected, namely kaempferol and its 3-O-β - D-glucoside, 7-O-β-D-glucoside, 3-O-α-L rhamnosyl, 7-O-β-D-glucoside, 3-O-rutinoside, 7- O-rutinoside, 3-O-α-L-rhamnoside and 3-O-β-D- galactorhamnoside as well as quercetin and its 3-O-α-L-rhamnoside and 3-O-rutinoside; four coumarins, namely 7-hydroxycoumarin (umbelliferone); 6,7-dihydroxycoumarin (esculetin); 6-methoxy-7-hydroxycoumarin (scopoletin) and 6-methoxycoumarin 7-O-glucoside (scopoletin 7-O-glucoside); the alkaloids tropine and its chloride salt; seventeen amino acids and eleven free sugars were also detected. The compounds were all identified through chemical and spectroscopic data including IR, UV, EI and CIMS, 1H and 13C NMR. The extracts showed moderate diuretic, tranquillizing, hypoglycemic, antihemorrhagic activity, in addition to antibacterial and antifungal effects. The extracts showed negative antiasthmatic effects and were found to be safe for liver and kidney functions; they also act to relieve intestinal and uterine pain.